PERBEDAAN KUMUR CHLORHEXIDINE TERHADAP SKOR GINGIVITIS PASIEN ORTHO CEKAT USIA 15- 30 TAHUN DI PRAKTEK Drg.SOFYAN MAKASSAR - Pariati Pariati; Suharyono Suharyono; Siti Hidayati (Journal of Oral Health Care, 2014)
Chlorhexidine is one mouthwash that potent and have antibacterial with broadspectrum. Effective against Gram positive and Gram negative though to the lasttype of the effectiveness a bit lower, but effectively reduce inflammation of the gingivaand the accumulation of plaque. Orthodontic treatments, including fixed orthodontic(ortho unfixed or fixed) nowadays is often used along with the rise of thesociety’s knowledge. Gingivitis periodontal, is a disease usually caused by plaque’smicroorganism and The products which result in the occurrence inflammatory andinfectious agent that destroys the supporting tissue of the teeth Including gingiva,ligament periodontal, the alveolar. The existence of other fixed orthodontic that stickto the teeth will complicate to cleaning the teeth so the tends to occur plaque buildupon the teeth around the bracket and one by the three crowns of the teeth on the edgeof gingiva. the good cleanliness of the teeth and mouth can be understood that teethand mouth free from any debris, calculus, plaque or other foreign material. This studyaimed to determine the difference of the chlorhexidine for 15-30 years old gingivitisscore fixed ortho patients in the practice of Drg Sofyan Makassar. The samplesretrieved from the population of 30 gingvitis subjects who use ortho fixed. Gargle hasbeen done at home for 7 days with gargle twice everyday after the subject has abrushing teeth in the morning and after the subject has a brushing teeth before sleepin the night. Then analyzed using statistical test of Paired Sample T Test. Based onstatistical analysis, there was a decrease in the degree of gingivitis and an differenceof the gingivitis score chlorhexidine for fixed ortho patients after gargle withchlorhexidine.